Peran Guru dalam Meningkatkan Kesadaran Siswa tentang Dampak Bullying di SMA Negeri 1 Pebayuran - Karyadi Karyadi; Aris Riswandi Sanusi; Tridays Repelita (Pusat Riset dan Inovasi Nasional, 2025)
The research aims to find out the role of Pancasila and Citizenship Education (PPKn) teachers in increasing student awareness of the impact of bullying behavior at SMA Negeri 1 Pebayuran, Bekasi Regency, West Java. The research uses a descriptive method with a qualitative approach. Data collection was carried out through observation and in-depth interviews. The informants in this study consisted of six people, namely the deputy principal for curriculum, two PPKn teachers, and three students (one male and two female). The interviews were conducted directly to obtain in-depth information about the role of PPKn teachers in educating and forming students' awareness of the negative impact of bullying. The results of the study show that PPKn teachers have an important role in improving students' understanding of human values, tolerance, and justice. These values are the basis for responding to and preventing bullying behavior in the school environment. PPKn teachers not only convey material theoretically but also instill moral values in students' daily lives.